Correlation between The Level of Independence of Elderly and Dementia in West Java - Faridho, Fikrifar Rizki; Yuniastuti, Ari; Zainafree, Intan (Universitas Negeri Semarang, 2024)
Dementia, which the sufferer is estimated to be 153 million people in 2050, is a public health problem, especially for the elderly, which will slowly make the sufferers more dependent on other people to do daily activities. The aim of this study is to analyze the correlation between the level of independence of the elderly and dementia in West Java. This study used a cross-sectional design using primary data from 68 elderly people in Sentra Terpadu Pangudi Luhur based on the inclusion and exclusion criteria. Univariate analysis showed that most respondents were young elderly (48.5%), males (55.9%), had no history of smoking (52.9%), no history of consuming alcohol (91.2%), had normal body mass index (58.8%), had hypertension (69.1%), did not have diabetes mellitus (92.6%), did not have depression (75%), had mild dependence (50%), and did not have dementia (50%). The results of the hypothesis test of the Rank Spearman correlation between the level of independence of the elderly and dementia showed a strong correlation in a significant positive direction with a correlation coefficient of 0.561. Daily physical activities with moderate intensity are required to prevent dementia.